The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.14778/1454159.1454227
|View full text |Cite
|
Sign up to set email alerts
|

Column-store support for RDF data management

Abstract: This paper reports on the results of an independent evaluation of the techniques presented in the VLDB 2007 paper "Scalable Semantic Web Data Management Using Vertical Partitioning", authored by D. Abadi, A. Marcus, S. R. Madden, and K. Hollenbach [1]. We revisit the proposed benchmark and examine both the data and query space coverage. The benchmark is extended to cover a larger portion of the query space in a canonical way. Repeatability of the experiments is assessed using the code base obtained from the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 3 publications
1
121
0
Order By: Relevance
“…The number of self-joins in the plan corresponds to the number of properties co-located in a table. The phenomenon is reminiscent of the debate concerning the use of row-stores vs. column stores [12,21,44,47]. Consideration of rowstores vs. column-stores is outside the scope of this paper.…”
Section: Self-join Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of self-joins in the plan corresponds to the number of properties co-located in a table. The phenomenon is reminiscent of the debate concerning the use of row-stores vs. column stores [12,21,44,47]. Consideration of rowstores vs. column-stores is outside the scope of this paper.…”
Section: Self-join Eliminationmentioning
confidence: 99%
“…Consideration of rowstores vs. column-stores is outside the scope of this paper. Nevertheless, we note that there is debate within the community on the use of row-stores or column-stores for native RDF data and our measurements may help ground that debate [12,21,44,47].…”
Section: Self-join Eliminationmentioning
confidence: 99%
“…Our attention also catch column-oriented databases [7,95], which can be customized for provenance management, and provenance reduction techniques [28], which can be used to decrease storage requirements via duplicate elimination and provenance inheritance. Finally, we would like to consider querying and managing scientific workflow provenance in distributed environments with multiple computing nodes to enable processing of huge datasets with billions of triples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other researchers can exploit this available software artifacts as a valuable starting point to evaluate and assess the significance of their own proposed contribution. One of the interesting examples for the value of such independent evaluation studies is the study of Sidirourgos et al [39] where they have reported about an independent assessment of the published result by Abadi et al in [4] which described an approach for implementing a vertically partitioned DBMS for Semantic Web data management. The outcomes of this independent assessment revealed many interesting aspects.…”
Section: Benchmarking Challenges In Computer Sciencementioning
confidence: 99%
“…For instance, in [4] Abadi et al reported that the performance of binary tables is superior to that of the clustered property table for processing RDF queries while Sidirourgos et al [39] reported that even in columnstore database, the performance of binary tables is not always better than clustered property table and depends on the characteristics of the data set. In addition, the experiments of [4] reported that storing RDF data in column-store database is better than that of row-store database while [39] experiments have shown that the gain of performance in column-store database depends on the number of predicates in a data set. A main lesson from this example is that we cannot really be sure that published research results are accurate and comprehensive even if they were reported by the best scientists and went through the most rigorous peer review process.…”
Section: Benchmarking Challenges In Computer Sciencementioning
confidence: 99%